Association between working memory performance and parent and teacher ratings of working memory in 11-year-old children born preterm - Haveri, Laura; Munck, Petriina; Leppänen, Jukka M.; Korpela, Satu; Haataja, Leena; Nyman, Anna H. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Working memory (WM) difficulties are often observed in children born preterm. We examined whether performance-based measures of WM components are associated with parent- and teacher-rated WM difficulties in the everyday life of children born very preterm and/or at very low birth weight (VPT/VLBW) at 11 years (n = 165). The WM components as defined in the original Baddeley's model - phonological loop (PL), visuospatial sketchpad (VS), and central executive (CE) - were assessed with tasks from the Working Memory Test Battery for Children (WMTB-C) and the Wechsler Intelligence Scale for Children - Fourth edition (WISC-IV). Parents and teachers completed the WM subscale of the Behavioral Rating Inventory for Executive Functions (BRIEF). Measures of WM components were modestly associated with BRIEF scores, explaining 18.9% of the variance in parent-rated and 14.0% of teacher-rated WM difficulties. CE was the component most consistently associated with parent- and teacher-rated everyday WM. To conclude, our results suggest that tasks that utilize CE functions may best reflect WM outside of controlled test settings in the follow-up of VPT/VLBW children. However, performance and rating-scale measures provide unique information and are both needed to comprehensively assess WM skills.